The Psychological Health and Wellbeing Benefits of Organised Sports and Physical Activities among Nigerian Prisoners - Ayobami Honestus Obadiora; Aderonmu Kehinde Adebayo (Universitas Ahmad Dahlan, 2019)
Imprisonment is a major factor responsible for personality disorders characterized by increased stress, depression, anxieties and chronic restlessness among inmates. The study investigates the impacts of active involvement in sports on the perceived psychological health by inmates of Ilesa Prison Yard in Osun State of Nigeria. The research is an experimental study through which the respondents were exposed to pretest instrument, intervention and the posttest questionnaire. This study held for 10 weeks during which a total number of 140 inmates were selected as respondents. The psychological wellbeing instrument of the Quality of Life scale (WHOQOL-BREF)of the World Health Organization (WHO) was modified and used in the investigation. The collected data were analyzed with both the inferential and descriptive statistics. The study showed positive impact of athletics (r=0.576), badminton (r=.544), table-tennis (r=.773), volleyball (r=.497) on the self-reported psychological health by male prisoners. The result is found significant at (P<0.05). In conclusion, it was postulated that participation in sport activities present positive impact on the perceived psychological health among the male prisoners in Nigerian prison yard, in Ilesa, Osun State of Nigeria.Â